PEMBERIAN IZIN TERHADAP PENJUALAN MINUMAN BERALKOHOL DITINJAU BERDASARKAN PERATURAN DAERAH KOTA SAMARINDA NOMOR 6 TAHUN 2003 TENTANG LARANGAN, PENGAWASAN, PENERTIBAN PENJUALAN MINUMAN BERALKOHOL - Muhamad Syamsudin (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT Permit as proof of legality to run a business, especially trading goods that are sold freely or goods whose trade is under government supervision. One of the merchandise which is controlled by the government is alcoholic drinks. Alcoholic drinks are included in the merchandise under surveillance because the effects of consuming alcoholic drinks can reduce or eliminate people's awareness and cause illness in the human body.This type of research used in this research is Normative law research. "Normative legal research (juridical normative) is a legal research method carried out by examining mere literature or secondary data.The results of the study stated that the Provisions for Granting Permits Against Alcoholic Beverage Sales Based on the Samarinda City Regulation Number 6 of 2013 Concerning Prohibition, Supervision, and Ordering of Sales of Alcoholic Beverages that the Socialization of the Samarinda City Regulation Number 6 of 2013 governing alcoholic drinks was basically well implemented. Basically, alcoholic drinks cannot be bought and sold outside the place that has obtained a permit or that has obtained a permit or that has been stipulated in Regional Regulation No. 6 of 2013, that in Samarinda there are still many alcoholic beverage sales without permits circulating freely in the community. Legal Consequences Against Alcoholic Beverage Sellers That Are Not In Accordance with Samarinda City Regional Regulation Number 6 the Year 2013 Regarding Prohibition, Supervision, Ordering of Sales of Alcoholic Beverages that the Satpol PP (Civil Service Police Unit) as law enforcers has cracked down on selling alcoholic beverages without permission with the prior permission first giving the sellers who netted a warning letter and confiscating their alcoholic beverages merchandise, if in the future they repeat it then the officer is not reluctant to give them the summons to come to court, then after that if they continue to violate then the Apparatus will impose sanctions in accordance with applicable legal regulations.Keywords: Alcohol, Permission, Prohibition